2015
DOI: 10.1002/ajhb.22683
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and markers of cardiovascular risk among low‐income African American youth

Abstract: Objectives Our study examines the relationship between perceived discrimination and levels of C-reactive Protein and blood pressure in low-income youth ages 10–15 years old. Methods Data were collected from 10–15 year old focal children and their mothers. Face-to-face interviews were implemented to collect data on stressors including experiences of everyday discrimination from youth. High sensitivity CRP in dried blood spot samples and diastolic and systolic blood pressure were also collected at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 71 publications
2
75
1
Order By: Relevance
“…Other studies have also observed null results when examining the effects of racism on health outcomes among African-Americans (Albert et al, 2008), although some positive associations have been found (Cunningham et al, 2012; Goosby et al, 2015). But our results are consistent with those from a 2015 meta-analysis, which found that racism and health associations were consistently weaker in studies of African-Americans, compared to other racial/ethnic groups (Paradies et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also observed null results when examining the effects of racism on health outcomes among African-Americans (Albert et al, 2008), although some positive associations have been found (Cunningham et al, 2012; Goosby et al, 2015). But our results are consistent with those from a 2015 meta-analysis, which found that racism and health associations were consistently weaker in studies of African-Americans, compared to other racial/ethnic groups (Paradies et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PD has been associated with inflammation among young adults, 30 midlife adults, 31 low-income black youths, 32 and older blacks, 33 although the Dallas Heart Study showed no relationship between PD and inflammation among blacks, Hispanics, and whites. 34 In other studies, the link between PD and inflammation was limited to specific subpopulations, including women anticipating a racial threat 35 and non-obese women.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological or psychological stress responses such as somatic symptoms are likely to vary among adolescent and young adult African American males based on individual factors such as their temperament, situational factors such as cognitive appraisal, and contextual factors (Ebata & Moos, 1994). As it pertains to contextual factors, evolving research indicates that stressors connected to the social status, race, and gender of young African Americans are related to negative physiological outcomes (e.g., Brody et al, 2014;Goosby, Malone, Richardson, Cheadle, & Williams, 2015;Grollman, 2012). It is important that future research account for contextual stressors, general stressful life events, as well as perceived stress to examine their relative contribution to somatic symptoms and other indicators of emotional and physical health among young African American males (e.g., Pieterse & Carter, 2007).…”
Section: Resultsmentioning
confidence: 99%